2019
DOI: 10.1002/smll.201804347
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treatment for Nitrogen‐Doped 3D Graphene Framework by a Conductive Matrix with Sulfur for High‐Performance Li–S Batteries

Abstract: Lithium ion batteries (LIBs) are widely used storage devices, which have a wide range of applications in electrical devices, hybrid electric vehicles, and for harvesting of renewable energy. [1] However, increasing demands for high-performance energy storage are unlikely to be satisfied by the theoretical capacities of the LIBs. [2] In particular, alternative cathode materials are required. [3] Recently, lithium-sulfur (Li-S) batteries have received attention owing to their high theoretical specificCarbon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 66 publications
(21 reference statements)
0
51
0
Order By: Relevance
“…Wearable energy storage devices, especially flexible supercapacitors, are getting extra attention due to their higher cycling stability and power density [1][2][3][4]. As for material systems of supercapacitor electrodes, recent researches mainly focus on three principle types: carbon-based high surface area materials (activated carbon, graphene, carbon fibers, and so on), transition metal oxides (MOs), and conducting polymers (CPs) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable energy storage devices, especially flexible supercapacitors, are getting extra attention due to their higher cycling stability and power density [1][2][3][4]. As for material systems of supercapacitor electrodes, recent researches mainly focus on three principle types: carbon-based high surface area materials (activated carbon, graphene, carbon fibers, and so on), transition metal oxides (MOs), and conducting polymers (CPs) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, heteroatom‐doped carbon was developed as a sulfur‐supporting host material and exhibited a chemical interaction between heteroatom and LiPS in the process . However, in order to maintain the outstanding conductivity, the doping amount was kept low (less than 10%), thus limiting the amount of LiPS adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recently, heteroatom-doped carbon was developed as a sulfur-supporting host material and exhibited a chemical interaction between heteroatom and LiPS in the process. [17][18][19][20][21][22][23] However, in order to maintain the outstanding conductivity, the doping amount was kept low (less than 10%), thus limiting the amount of LiPS adsorption. Simultaneously, it has been discovered that various transition metal sulfides with high polarities exhibited forceful chemisorption and excellent electrocatalysis, which availably alleviates the shuttle effect for Li-S cells.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of N atoms in carbon materials could signicantly enhance electrocatalytic activity, thus inducing efficient ORR. [15][16][17] In addition, previous reports have indicated that doping carbon materials with transition metals such as Co, Fe, Ni, etc. is also an effective way to improve the catalytic performance of the catalyst.…”
Section: Introductionmentioning
confidence: 99%